Fragilidade e sua associação com desfechos de saúde bucal em adultos e idosos no Brasil - Vasconcellos, Natália Boessio Tex de (2022)
Faced with advances in the demographic transition and population aging, frailty must be taken into account both in clinical practice and in research on aging. The most accepted and widespread conceptual definition in the scientific community is that frailty is a multidimensional biological syndrome characterized by a reduction of multiple physiological systems, making it difficult for the individual to adapt to stressors, generating a state of vulnerability that causes numerous adverse health outcomes. , including functional decline, hospitalization, disability, long-term care, and death. The oral health of the elderly becomes potentially more complicated as they become more fragile and due to disabilities and dependency on care derived from it. It is noteworthy that there are no Brazilian studies, nationwide, assessing frailty and oral health outcomes. Therefore, the objective of this thesis is to evaluate the association between frailty and the use of dental services, as well as to evaluate the mediating effect of frailty on self-perception of oral health. Data are obtained from the baseline of the ELSI Brasil (Longitudinal Health Study of the Brazilian Elderly), with a representative sample of the Brazilian population aged over 50 years. Data collection took place between 2015 and 2016. Demographic, socioeconomic, biological and oral health variables were collected through a household, individual questionnaire and physical measurements. Frailty was assessed according to the Frailty Phenotype based on five criteria: weight loss, exhaustion, slow gait speed, weakness and low level of physical activity. The presence of three or more criteria the individual is considered frail. In the presence of two or one component, the individual is considered pre-frail and robust when there are no components. The variables of self-perception of oral health and use of dental services were self-reported. Data were analyzed using the statistical programs STATA 14 and Mplus version 6.12. Poisson regression was used using the svy command to obtain crude and adjusted prevalence ratios to assess the association between frailty and use of dental services. Structural Equation Models verified the mediating effect of frailty on self-perceived oral health. The ELSI-Brasil was approved by the Brazilian National Research Ethics Committee and the final sample size was 9,412 individuals. The results of this thesis showed that being frail is associated with not using dental services in the last year. It was also observed that frailty has a direct path and is a mediator between socioeconomic status (SEP) and self-perception of oral health in Brazilian adults and elderly people, that is, individuals with low SEP showed greater frailty and individuals with greater frailty presented worse self-perception of oral health. In conclusion, frailty is an important variable both in research and in clinical situations and that must be taken into account when planning oral health promotion and prevention. Given the complexity of oral health determinants, frailty adds another dimension to be examined in the elderly. Public health strategies that consider a common approach to risk factors should be endorsed.